Specific Telic Constructions with the Preposition do in Serbian - Ašić, Tijana V.; Grujić, Tatjana S.; Kebara, Marina V. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
This paper examines the specifics of the Serbian preposition do [to] in so-called telic constructions, which express the involvement of the sentence subject in collective activities related to a location (ground). The authors demonstrate that, unlike the prototypical prepositions u [in], na [on], and kod [at], the Serbian preposition do indicates, due to its reinterpretation as expressing dynamic spatial relations, that the subject has reached a particular location (or area of the ground) with the intention of achieving a specific goal, but that their presence at this location will be relatively brief. This characteristic suggests that the subject’s intention can be connected to a telic interpretation. If the intention cannot be associated with this interpretation, the reasons for the subject’s behavior can be inferred from the context or explicitly stated.